Nephrology and fluid/electrolyte physiology : neonatology questions and controversies - Oh, William ;Guignard, Jean-Pierre ;Baumgart, Stephen ;Polin, Richard A. (Philadelphia, Pennsylvania : Elsevier, Saunders, 2012)
Nephrology and Fluid/Electrolyte Physiology, a volume in Dr. Polin's Neonatology: Questions and Controversies Series, offers expert authority on the toughest neonatal nephrology and fluid/electrolyte challenges you face in your practice. This medical reference book will help you provide better evidence-based care and improve patient outcomes with research on the latest advances. Reconsider how you handle difficult practice issues with coverage that addresses these topics head on and offers opinions from the leading experts in the field, supported by evidence whenever possible. Find information quickly and easily with a consistent chapter organization. Get the most authoritative advice available from world-class neonatologists who have the inside track on new trends and developments in neonatal care. Purchase each volume individually, or get the entire 6-volume set, which includes online access that allows you to search across all titles!
The placenta and fetal amniotic fluid volume : understanding fetal water flow / Michael G. Ross -- Body fluid changes in the fetus and newborn : normal transition / William Oh -- Renal aspects of sodium metabolism in the fetus and newborn / Endre Sulyok -- Potassium metabolism / John M. Lorenz -- Renal urate metabolism in the fetus and newborn / Daniel I. Feig -- Perinatal calcium and phosphate metabolism / Reginald Tsang and Ran Namgung -- Acid-base homeostasis in the fetus and newborn / Istvan Seri -- Glomerular filtration rate in neonates / Jean-Pierre Guignard -- The developing kidney and the fetal origins of adult cardiovascular disease / Umberto Simeoni -- Renin-angiotensin-aldosterone system (RAAS) : renal modulation / Pedro A. Jose -- Renal modulation : arginine vasopressin and atrieal natriuretic peptide / Francesco Emma -- Acute problems of prematurity : balancing fluid volume and electrolyte replacement in very low birth weight and extremely low birth weight neonates / Stephen Baumgart -- Lung fluid balance in developing lungs and its role in neonatal transition / Lucky Jain and Sarah D. Keene -- Use of diurects in the newborn / Jean-Pierre Guignard -- Neonatal hypertension : diagnosis and management / Joseph Flynn -- Edema / Andrew Costarino and Yosef Levenbrown -- Renal failure of the neonate / Sharon P. Andreoli -- Congenital tubulopathies / Israel Zelikovic -- Obstructive uropathies : assessment of renal function in the fetus / Robert L. Chevalier
Includes bibliographical references and index.
Keywords: INFANT, NEWBORN, DISEASES